2003
DOI: 10.1111/j.1349-7006.2003.tb01405.x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of mature dendritic cells fully capable of T helper type 1 polarization using OK‐432 combined with prostaglandin E2

Abstract: endritic cells (DCs) are very potent antigen-presenting cells, which play central roles in bridging between innate and acquired immunity via direct cell-cell interactions and/or cytokine production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 33 publications
3
36
0
Order By: Relevance
“…OK-432 has been reported to be useful for stimulating DCs in terms of maturation (14,(17)(18)(19)23,24,26). In the present study, we also showed that OK-432 stimulated immature DCs to acquire a mature phenotype and to produce significant amounts of Th1-type cytokines such as IL-12 and IFN-γ.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…OK-432 has been reported to be useful for stimulating DCs in terms of maturation (14,(17)(18)(19)23,24,26). In the present study, we also showed that OK-432 stimulated immature DCs to acquire a mature phenotype and to produce significant amounts of Th1-type cytokines such as IL-12 and IFN-γ.…”
Section: Discussionsupporting
confidence: 80%
“…Mature DCs are believed to induce T cell immunity, whereas the immature development stages of DCs are thought to induce T-cell anergy or regulatory T cells (14)(15)(16) (14,(17)(18)(19). Our previous studies emphasized that the Th1 immune reaction was the most important to activate CTLs in a DC-based immunotherapy (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…On day 2 and 4 of culture, floating cells were gently removed and fresh medium with cytokine was replaced. Monocyte-derived DCs were generated from peripheral mononuclear lymphocytes (PBMCs) using standard method as described before (23). Briefly, PBMCs were plated in 100x20-mm tissue culture plates at the density of 2.0x10 7 cells per dish in 5 ml of RPMI-1640 medium without serum.…”
Section: Generation Of Murine Bone Marrow Derived Dcs (Bm-dcs)mentioning
confidence: 99%
“…2B). Indeed, we measured surface expression of CD83, which is expressed by mDCs (34), DC-SIGN, which is a calcium-dependent pattern-recognition lectin reported to be predominantly expressed on iDCs (35), HLA-DR, which has been reported to be upregulated on DC maturation (26), and finally CCR7, which is associated with maturation of DCs and promotes their migration from tissues to lymphoid organs (36). When compared with iDCs, LPS/IFN-g-induced maturation of DCs is characterized by a significant increase in CD83 (442 6 2.4 versus 14 6 3. in monocytes subjected to a treatment with sHZ and GM-CSF/IL-4, which is in agreement with previous findings (37,38).…”
Section: Resultsmentioning
confidence: 99%